2007
DOI: 10.1242/jcs.007443
|View full text |Cite
|
Sign up to set email alerts
|

Polarity proteins PAR6 and aPKC regulate cell death through GSK-3β in 3D epithelial morphogenesis

Abstract: Epithelial cells are polarized, with an apical surface facing a lumen or outer surface and a basolateral surface facing other cells and extracellular matrix (ECM). Hallmarks of epithelial carcinogenesis include loss of polarity, as well as uncontrolled proliferation and resistance to apoptosis. Are these features controlled by a common molecular mechanism? The partitioning-defective 3 (PAR3)-PAR6-atypical PKC (aPKC) complex is a master regulator that controls polarization in many animal cells. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 58 publications
5
64
0
Order By: Relevance
“…24,42 However, recent studies have revealed that proliferation and apoptosis are coupled to the polarity function of this complex and activated downstream. 43,44 Interestingly, we found that in contrast to the marked inhibition of proliferation that occurred in Cdc42 deficient acini in 3D cultures, cell cycle progression was unaffected when the knockout cells were grown as monolayers on tissue culture plastic. These results suggest that proliferation in the Cdc42 deficient acini is affected by environmental cues from the 3D culture environment that promotes polarity establishment 45 and further suggest a role for the Cdc42/Par/ PKCζ polarity complex in promoting MEC proliferation during acinus morphogenesis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…24,42 However, recent studies have revealed that proliferation and apoptosis are coupled to the polarity function of this complex and activated downstream. 43,44 Interestingly, we found that in contrast to the marked inhibition of proliferation that occurred in Cdc42 deficient acini in 3D cultures, cell cycle progression was unaffected when the knockout cells were grown as monolayers on tissue culture plastic. These results suggest that proliferation in the Cdc42 deficient acini is affected by environmental cues from the 3D culture environment that promotes polarity establishment 45 and further suggest a role for the Cdc42/Par/ PKCζ polarity complex in promoting MEC proliferation during acinus morphogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…38,43 Thus, increased apoptosis in the Cdc42 knockout acini may also have been affected by disruption of the polarity complex. α6 integrin was also mislocalized in the Cdc42 deficient acini at later time points, suggesting a failure of the acini to maintain proper attachment to extracellular matrix proteins (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we incubated MDCK cells with myristoylated PZI. PZI is specifi c for aPKC and has been used to disrupt polarityrelated processes in MDCK cells ( 36 ). Treatment with PZI by itself reduced the number of primary cilia to 20% of the control value ( Fig.…”
Section: Ceramide Activation Of Apkc Is Critical For Ciliogenesismentioning
confidence: 97%
“…Cdc42 is required by Madin-Darby canine kidney (MDCK) cells to form tubules in three-dimensional (3D) culture by regulating the formation of the apical plasma membrane domain and tight junctions as well as primary ciliogenesis (Choi et al, 2013;Kim et al, 2007;Rodriguez-Fraticelli et al, 2010;Rogers et al, 2003;Zhang et al, 2001;Zuo et al, 2011). Two studies have shown that Cdc42 is essential for normal kidney development and function.…”
Section: Introductionmentioning
confidence: 99%